2021
DOI: 10.1177/14604582211052253
|View full text |Cite
|
Sign up to set email alerts
|

Teams managing civilian and military complex trauma: What are the competencies required in austere environments and the potential of simulation technology to address them?

Abstract: Surgical training in civilian hospitals may not be sufficient for managing complex trauma in a setting where such care is not commonly practiced. Understanding the challenges that civilian teams face when moving to austere environments can inform the competencies that need to be trained. The aim of this study was to explore the competencies required in austere environments for teams managing complex trauma, and how they can be trained with simulation technologies. Ethnographic field observations were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…24 Team members may find themselves working with unfamiliar equipment, personnel or infrastructure. 24 Despite all these challenges overlaid on a high stakes environment, clinicians must be able to assimilate data to gain situational awareness, which is the anchor for most cognitive and interpersonal competencies for management of trauma patients. 25 The red line culture was the antithesis of an environment which fostered situational awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Team members may find themselves working with unfamiliar equipment, personnel or infrastructure. 24 Despite all these challenges overlaid on a high stakes environment, clinicians must be able to assimilate data to gain situational awareness, which is the anchor for most cognitive and interpersonal competencies for management of trauma patients. 25 The red line culture was the antithesis of an environment which fostered situational awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary simulation laboratories for trauma resuscitation with an emphasis on team performance and NTS can build on teamwork concepts that are introduced in ATLS. 24,[29][30][31] Monthly multidisciplinary trauma conferences and video case reviews of trauma resuscitation led by EPs and trauma surgeons could use previous cases to create simulation scenarios that provide formative learning for technical and NTS. 5) Include EPs in trauma focused surgical courses.…”
Section: Discussionmentioning
confidence: 99%
“…Third, medical professionals’ background in training and experience should be considered during the composition of medical teams for deployment, ensuring a representation of complementary skills. Competency lists have been established for deployed teams providing damage control surgery in austere environments [ 9 , 47 ], and an essential addition was made by Stathakarou et al ., who included nontechnical competencies [ 48 ]. Application of a competency checklist before deployment facilitates identifying the need for additional customised training or simultaneous deployment of medical professionals with complementary skills.…”
Section: Discussionmentioning
confidence: 99%
“…We will include both qualitative and quantitative empirical and design studies that address different types of simulation interventions, identified in our previous study [ 10 ], which incorporate game elements. Game elements will be identified using published gamification frameworks [ 14 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Different simulation technologies can be used to train different competencies in trauma [ 9 ]. A previous study [ 10 ] identified examples of emerging technologies used for trauma training that have the potential to support the education and training toward challenges that civilian trauma teams face when moving to an austere environment. Examples included virtual reality, virtual reality combined with haptics and manikins or requiring special equipment, virtual patients, and gamification.…”
Section: Introductionmentioning
confidence: 99%